Pain experiences of patients with musculoskeletal pain + central sensitization: A comparative Group Delphi Study. - Axel Georg Meender Schäfer; Leonie Johanna Joos; Katharina Roggemann; Kerstin Waldvogel-Röcker; Michael Pfingsten; Frank Petzke (PLoS ONE)
Objectives Central sensitization (CS) is regarded as an important contributing factor for chronification of musculoskeletal pain (MSP). It is crucial to identify CS, as targeted multimodal treatment may be indicated. The primary objective of this study was therefore to explore pain experience of individuals with MSP+CS in order to gain a better understanding of symptoms in relation to CS from a patient perspective. The secondary objective was to investigate whether pain experiences of patients with MSP+CS differ from those of individuals with neuropathic pain (NP). Methods We conducted a comparative Group Delphi Study including patients with MSP+CS and neuropathic pain (NP). 13 guiding questions were used to gather information about sensory discriminatory, affective and associated bodily, mental and emotional phenomena related to the pain experience of patients. Descriptions were categorized using qualitative content analysis. Additionally, patients completed several pain related questionnaires. Results Nine participants with MSP+CS and nine participants with NP participated. The Delphi procedure revealed three main themes: psycho-emotional factors, bodily factors and environmental factors. Descriptions of patients with MSP+CS showed a complex picture, psycho-emotional factors seem to have a considerable impact on pain provocation, aggravation and relief. Impairments associated with mental ability and psyche affected many aspects of daily life. In contrast, descriptions of patients with NP revealed a rather mechanistic and bodily oriented pain experience. Discussion Patients with MSP+CS reported distinct features in relation to their pain that were not captured with current questionnaires. Insight in patient's pain experience may help to choose and develop appropriate diagnostic instruments.